(untitled) (Perner’s Contacts, 2016)
The paper describes transport accidents in the EU in recent years. Accidents which can happen through transportation of persons and freight can endanger human life, property and the environment. Accident statistics display injuries and fatalities, according to transport mode (air, road, water and rail transport)